2019
DOI: 10.1016/j.jcta.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Gessel polynomials, rooks, and extended Linial arrangements

Abstract: We study a family of polynomials associated with ascent-descent statistics on labeled rooted plane k-ary trees introduced by Gessel, from a rook-theoretic perspective. We generalize the excedance statistic on permutations to maximal nonattacking rook placements on certain rectangular boards by decomposing them into boards of staircase shape. We then relate the number of maximal nonattacking rook placements on certain skew boards to the number of regions in extended Linial arrangements by establishing a relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this paper, we shall state a bijection between rook placements on 2δ n and increasing binary trees on n + 1 vertices. Our bijection is rather simple, and is, in fact, a special case of a bijection constructed by Tewari in [14]. Tewari's bijection is between maximal rook placements on the board (n − 1) × kn and labelled rooted plane k-ary trees.…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, we shall state a bijection between rook placements on 2δ n and increasing binary trees on n + 1 vertices. Our bijection is rather simple, and is, in fact, a special case of a bijection constructed by Tewari in [14]. Tewari's bijection is between maximal rook placements on the board (n − 1) × kn and labelled rooted plane k-ary trees.…”
Section: Introductionmentioning
confidence: 95%
“…Note that the ascent-descent statistics on labeled binary trees were first studied in unpublished work by Gessel, and functional equations for their distribution were established by Kalikow [28] and Drake [12]. Given the striking observations of Gessel [16] relating the distribution of these statistics to enumerative questions in the theory of hyperplane arrangements, much work has been done recently [7,11,14,17,44]. That said, we will not focus on the hyperplane arrangements perspective in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The first author observed that certain evaluations of B n coincide with the number of regions in various well-known deformations of Coxeter arrangements [21]. This viewpoint has been pursued in [10,15,60], and a complete explanation has been offered by Bernardi [7]. Given a subset A of t´1, 0, 1u, we can consider the arrangement in R n consisting of all hyperplanes x i ´xj " a where i ă j and a P A.…”
Section: Introductionmentioning
confidence: 99%